Production, Purification and Characterization of Extra Cellular Lipase from Serratia marcescens and its Potential Activity for Hydrolysis of Edible Oils - Zaki, Neihaya H; Saeed, Sinan E (Al-Nahrain Journal of Science, 2018)
Twelve isolates of Serratia marcescens 32.4% were obtained out of 37 soil samples. One isolate (Serratia marcescens N3) was selected according to high lipase production. Lipase of this isolate was produced in liquid medium, extracted and purified by two stages included: CM-cellulose and DEAE-cellulose column, the fold of purification for the enzyme eluted from DEAE column was 19.33 with 61.15% recovery. The optimum pH and temperature for enzyme activity was 8 at 35°c, but it lost most of its activity (62%) at pH 10 and (78%) at 65°c.The effect of some metal ions and surfactant on lipase activity was also studied, since the presence of Ca+2 was more effective than that of Mg+2 in increasing lipase activity, and this indicate that lipase is a metalloenzyme. Surfactant like Tween 80 induced lipase activity (110%) followed by tween 20 (102%) while α –naphtholrin inhibited it to 21%.The activity of Serratia marcescens N3 lipase to hydrolyse different kinds of edible oils was determined, maximum activity appeared with Gingily oil followed by olive oil, coconut, sesame, soybean, and sunflower were (122, 112, 104, 93, 92 and 82) U/ml respectively.